Design And Build E-Therapy During The Pandemic Using An Android-Based User-Centred Design Model - Feby Riwindi Silitonga; Ristya Febriani Br Karo Sekali; Stefania Gracella Simamora; Marlince NK Nababan (Journal of Computer Networks, Architecture and High Performance Computing, 2021)
Therapy is a treatment to restore health to people who are sick such as mental disorders, many factors make people's psychological disorders today, one of which is the corona virus which is being experienced by many Indonesian people and even the world which has a negative impact. When people are infected with the corona virus, many experience depression, and this also has a negative impact on students at the University. The purpose of this research is to develop an application that can reduce the anxiety of people affected by the corona virus and aims to relax the human brain. And not only for people affected by Covid but also for the community as a tool for self-reflection. This application is designed to meet the needs of users affected by the corona virus. To make products more accessible to users, User-centered design (UCD) is a design process model that prioritizes user needs following user needs. From some people who have been exposed to the corona virus, the research team tries to respond to applications that have been developed. From the results of this study, the authors can conclude that from several characteristics of existing therapy, Muslim motivation is the most popular type of therapy with a test rate of 88.5% while the lowest test rate is Christian motivation with 57%.